Parents Role in Providing Health Care for Their Children (Analytical Study of Smoking Parents and Children) - Alosoufe, Laith; Al_Shatnawi, Feda’a; Abu-Shaika, Hayat; Jakalat, Suad (International Journal of Membrane Science and Technology, 2023)
The health consequences of smoking are well-known, and yet, children continue to smoke, placing their health and well-being at risk. Parents of smoking children play a crucial role in facilitating healthcare for their children and promoting healthy habits. However, caring for smoking children can be challenging, and parents who smoke face several unique challenges when providing healthcare for their children. This study aimed to explore the challenges faced by parents of smoking children when providing healthcare for their children and to identify potential intervention strategies that can facilitate better healthcare provision. A qualitative research design was used, and semi-structured interviews were conducted with 15 parents who had smoking children. Thematic analysis was performed to identify common patterns and themes in the data. The study found that parents face several challenges when caring for their smoking children, including difficulty in communicating with their children about smoking, worry about the negative health effects of smoking, difficulty in accessing healthcare services, inadequate parental education, and limited availability of family-friendly work environments. Parents highlighted the need for multi-pronged approaches to address these challenges, including parental education programs, health promotion campaigns, policy advocacy, and the use of technology. Parental education programs can empower parents by providing them with knowledge and skills to manage and prevent smoking in their children. Health promotion campaigns can reinforce the benefits of healthy habits and promote a smoke-free environment. Policy advocacy can facilitate changes in policies and regulations to improve healthcare access and support family-friendly work environments. The use of technology, such as telemedicine, can provide parents with access to healthcare services from the comfort of their homes. In conclusion, caring for smoking children can be challenging for parents who smoke. This study highlights the need to develop tailored intervention strategies to address the challenges faced by parents and to improve healthcare provision for smoking children. The recommended intervention strategies can help parents to better manage and prevent smoking in their children and promote healthy habits, leading to improved health outcomes for smoking children. Further research is needed to evaluate the effectiveness of these intervention strategies in improving healthcare provision for smoking children.